SOIL EROSION ESTIMATION USING THE EPM MODEL - Efthimiou, N.; Lykoudi, E. (Bulletin of the Geological Society of Greece, 2016)
The study aims to evaluate soil erosion and investigate its spatial distribution by applying the empirical EPM (i.e. Erosion Potential Model) at mountainous Mediterranean type catchments. Study area includes the catchments of Venetikos; Kalamas; Upper Acheloos and Arachthos Rivers (eight subcatchments in total), very important aquatic systems of NW Greece. The model was implemented both annually and inter-annually. A GIS-based approach was adopted, considering the spatial variation of its factors, as well as the erosion processes occurring in a catchment. The results were initially validated by being compared to the observed sediment yield values (based on the sediment discharge measurements conducted by the PPC). The model’s performance was poor, significantly underestimating the results at both time scales. The ambiguous reliability of the PPC measurements led to their replacement by simulated ones, estimated using the sediment discharge rating curves methodology. Regarding the latter, the model performed better, attributing more accurate results, yet anew underestimated. However, it managed to identify the most susceptible to erosion areas. The poor performance is mainly attributed to its inherent shortcomings along with the specific characteristics and sedimentary regime of the study area.